Temperature Effect on Mohr–Coulomb’s Effective Strength Parameters of Paste Backfill - Hasan, Alsidqi; Ting, Wee Kiet (Frontiers in Materials, 2022)
In-stope paste backfill monitoring at different mine sites showed anomalous increase in total stress during rest periods. One of the explanations according to a recent laboratory- model experiment was attributed to volumetric expansion caused by temperature increase within the backfill. This paper extends the understanding whether the Mohr–Coulomb’s effective strength parameters are affected by such temperature increase. The effects are explained through evaluating the apparent cohesion and the effective internal and interfacial friction angles under different temperature conditions. A series of modified direct shear tests were performed on saturated specimens under three controlled temperature levels: 25°C, 50°C, and 70°C. The specimens consist of cemented paste backfill and uncemented paste backfill. The results show that the effective internal and the interfacial friction angles increase as the temperature increases, depending on the type of material and the shearing condition, whereas the temperature increase does not significantly affect the apparent cohesion. The findings serve as a reference for engineers and academics in explaining the stress anomaly and to better understand the shear behavior of paste backfill under different temperature conditions for mine stope backfill design.